Dragons and mythical creatures - Osborne, Mary Pope; Boyce, Natalie Pope (Magic tree house fact tracker., 2015)
Returning from their adventures in Night of the Nine Dragons, Jack and Annie track the facts about favorite creatures from myth and legend, including dragons, mermaids and unicorns.